Nuansa Timur dalam Post-Punk : Analisis Lagu ‘Sukatani’ Karya Sukatani Band - Lutfi Ramadhiansyah; Abdul Rachman (Jurnal Riset Rumpun Seni, Desain dan Media, 2025)
This article analyzes the song "Sukatani" by Sukatani Band as a form of musical expression that represents Eastern nuances within a post-punk aesthetic framework. The research was conducted using a qualitative-descriptive approach through a music analysis method based on Jan LaRue's theory in Guidelines for Style Analysis (1970), which includes six main parameters: melody, harmony, rhythm, texture, form, and instrumentation. This analysis aims to reveal how the musical elements in the song can be read as a meeting between the post-punk idiom born in the West and the local socio-cultural context in Indonesia. The research findings show that "Sukatani" combines a minor pentatonic scale and repetitive structure as distinctive Eastern musical characteristics, while maintaining the monotonous and intense impression synonymous with post-punk aesthetics. From a lyrical perspective, the use of ngapak language not only strengthens local identity but also presents an authentic expression close to the daily lives of rural communities. The lyrics voice social criticism regarding class inequality, state repression, and respect for peasant labor as the foundation of collective life. Thus, music is not merely an aesthetic medium, but also a means of articulating cultural resistance against the dominance of central discourse and the hegemony of mainstream popular culture. Furthermore, analysis of texture and instrumentation reveals a combination of distorted guitars, repetitive bass patterns, and rigid drum beats, all of which create a tense yet meditative atmosphere.